THE ANALYSIS OF FACTORS INFLUENCING INTENTION TO USE PAY LATER USING TECHNOLOGY ACCEPTANCE MODEL (TAM) - Jagadhita, Putu Agus Arya; Tjhin, Viany Utami (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Financial Technology has changed the payment method in Indonesia which PayLater has become one of the most popular financial products in Indonesia. The users of PayLater have risen since the covid pandemic. In addition, it appears there are issues in the use of PayLater. The users reported their account have been hacked. Despite of the similarity of PayLater and credit card, the trend of PayLater has been increasing since 2021. The study wants to analyse the factors that PayLater has been popularly used on e-commerce but still at lower rank than other payment options and the consideration of users that know the risks that affect the intention to use of users. The purpose of the study is to know that there are factors that affecting the intention to use PayLater on e-commerce. The study adopts variables from Technology Acceptance Model (TAM) and combines with perceived risk variable and trust as mediate variable. The data collection was conducted through an online questionnaire and obtained from 252 respondents. The data was calculated using SmartPLS. The result shows that Perceived Usefulness, Perceived Ease of Use and Trust have a positive effect on the intention to use PayLater and Trust is considered to be partial mediation for Perceived Usefulness and Perceived Ease of Use.